2020
DOI: 10.1002/ece3.6015
|View full text |Cite
|
Sign up to set email alerts
|

Population‐specific effect of Wolbachia on the cost of fungal infection in spider mites

Abstract: Many studies have revealed the ability of the endosymbiotic bacterium Wolbachia to protect its arthropod hosts against diverse pathogens. However, as Wolbachia may also increase the susceptibility of its host to infection, predicting the outcome of a particular Wolbachia-host-pathogen interaction remains elusive. Yet, understanding such interactions and their eco-evolutionary consequences is crucial for disease and pest control strategies. Moreover, how natural Wolbachia infections affect artificially introduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 88 publications
(118 reference statements)
2
14
0
Order By: Relevance
“…For Experiment 2, Ru1 came from the previous antibiotic treatment but Gu and Ru2 were obtained from new treatments performed in September 2016 and January 2017, respectively. In this case, 300 Gi or Ri2 adult females were installed in petri dishes containing fragments of bean leaves placed on cotton soaked in a rifampicin solution (0.05%, w/v) for one generation (Gotoh et al 2005;Zélé et al 2020a). All antibiotic treatments were performed in the same standard conditions as population rearing (24±2ºC, 16/8h L/D).…”
Section: Antibiotic Treatmentsmentioning
confidence: 99%
“…For Experiment 2, Ru1 came from the previous antibiotic treatment but Gu and Ru2 were obtained from new treatments performed in September 2016 and January 2017, respectively. In this case, 300 Gi or Ri2 adult females were installed in petri dishes containing fragments of bean leaves placed on cotton soaked in a rifampicin solution (0.05%, w/v) for one generation (Gotoh et al 2005;Zélé et al 2020a). All antibiotic treatments were performed in the same standard conditions as population rearing (24±2ºC, 16/8h L/D).…”
Section: Antibiotic Treatmentsmentioning
confidence: 99%
“…The outcome of entomopathogenic infections is often defined by pathogen virulence, and host genotype. However, other host-associated microbiota can have significant impact on hostpathogen interactions [48][49][50]. This can be particularly true with naturally occurring symbionts, such as Wolbachia, which have evolved to be intimately associated with their insect hosts [51].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, spider mite (Tetranychus urticae) populations naturally infected with Wolbachia presented variable effects of fungal infection when challenged with Metarhizium brunneum and B. bassiana. While neither of these fungal entomopathogens had any effect on one spider mite population, Wolbachia presence led to an increase in mortality when a different mite population was challenged with B. bassiana [48]. In addition, a study conducted with the fruit fly Drosophila melanogaster reported a protective effect of Wolbachia against infection with the entomopathogenic fungus Beauveria bassiana [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Experiment 2, Ru1 came from the previous antibiotic treatment but Gu and Ru2 were obtained from new treatments performed in September 2016 and January 2017, respectively. In this case, 300 Gi or Ri2 adult females were installed in petri dishes containing fragments of bean leaves placed on cotton soaked in a rifampicin solution (0.05%, w/v) for one generation (Gotoh et al 2005; Zélé et al 2020a). All antibiotic treatments were performed in the same standard conditions as population rearing (24±2°C, 16/8h L/D).…”
Section: Methodsmentioning
confidence: 99%